Association between low-carbohydrate diet score and incidence of type 2 diabetes among Japanese adults: the JACC Study - Akinori Yaegashi; Takashi Kimura; Takumi Hirata; Hiroyasu Iso; Akiko Tamakoshi (Journal of Nutritional Science, 2023)
We prospectively examined the association between low-carbohydrate diet (LCD) score and incidence of type 2 diabetes (T2D) in Japanese adults using Japan Collaborative Cohort Study for Evaluation of Cancer Risk (JACC Study) data. A total of 19 084 (7052 men and 12 032 women) Japanese non-diabetic participants aged 40–79 years, who enrolled in the JACC study between 1988 and 1990, were included in our analysis. Dietary intake was evaluated using a validated food-frequency questionnaire. The overall, animal and vegetable LCD scores were calculated by dividing the study participants into eleven categories based on the percentages of energy from carbohydrates, protein and fat. The incidence of T2D was assessed using a self-administered questionnaire. We used multivariable logistic regression analysis to estimate the odds ratios (ORs) and 95 % confidence intervals (CIs) of incident T2D across the quintile of each LCD score, with adjustment for potential confounders. During the 5-year study period, 490 adults (247 men and 243 women) developed T2D. The multivariable-adjusted OR of incident T2D for the highest v. lowest quintiles of overall and animal LCD scores, respectively, were 0·64 (95 % CI 0·42, 0·99) and 0·83 (95 % CI 0·55, 1·27) for men, 0·78 (95 % CI 0·51, 1·18) and 0·84 (95 % CI 0·57, 1·24) for women. The vegetable LCD score was associated with a lower risk of T2D in men (OR 0·51; 95 % CI 0·33, 0·77). Our results suggest that diets lower in carbohydrates and higher in fat and protein are unlikely to higher the T2D risk among Japanese individuals.